Study the effect of some environmental factors on the assimilation of sugars by N2 FIXING Cyanobacterium mastigocladus lamious - Osama Naji Ahmed; Hameed Salman Khamees (Tikrit Journal of Pure Science, 2023)
The effect of some sugars(Glucose, fructose, mannose, sucrose, Ribose, mannitol, xylose) in different concentrations 1,2,3 mg/ ml on growth of species Mastigocladus lamious  under continuous light and alternative light and darkness period (8 light,16 darkness)h , Result showed that sugars in all concentrations  had needs a period of time to adapts for some concentrations themself before it can metabolize.